Towards reliable virtual-surgery in virtual environments : achievements, challenges and design guidelines - Muhammad Shafie Abd. Latiff 560524; Imran Ghani; International Conference on Computer Graphics and Multimedia (2nd : 2004 : Bangi, Selangor) 476312 (Skudai : Universiti Teknologi Malaysia, 2004)
57